Positron emission tomography imaging in cardiovascular disease. Issue 22 (22nd June 2020) - Tarkin, Jason M; Ćorović, Andrej; Wall, Christopher; Gopalan, Deepa; Rudd, James HF
Abstract : Positron emission tomography (PET) imaging is useful in cardiovascular disease across several areas, from assessment of myocardial perfusion and viability, to highlighting atherosclerotic plaque activity and measuring the extent of cardiac innervation in heart failure. Other important roles of PET have emerged in prosthetic valve endocarditis, implanted device infection, infiltrative cardiomyopathies, aortic stenosis and cardio-oncology. Advances in scanner technology, including hybrid PET/MRI and total body PET imaging, as well as the development of novel PET tracers and cardiac-specific postprocessing techniques using artificial intelligence will undoubtedly continue to progress the field.